Studi Literatur tentang Perilaku Imitasi Pengguna Media Sosial TikTok di Kalangan Remaja (Prosiding Konseling Kearifan Nusantara (KKN), 2025)
This study examines imitation behavior among adolescent TikTok social media users, focusing on the factors that influence it and its impact on adolescent social and psychological development. In the digital era, TikTok has become a popular platform that facilitates the spread of viral trends and challenges, which are often followed by adolescents. Through the literature study method, this research analyzes various literatures related to social media influence, self-identity, and imitation behavior. The results show that social influence, exposure to viral content, and the need to gain recognition from peer groups are the main drivers of imitation behavior on TikTok. This imitation behavior brings positive impacts, such as increased creativity and social interaction, but also risks reducing originality and causing social pressure. This study suggests the need for digital literacy education to help adolescents manage social media use wisely and maintain an authentic self-identity amidst the strong influence of digital culture.